Shariah Governance, Reputation and Customer Loyalty of Islamic Banks - Nanda Suryadi; Muhamad Albahi; Norman Gisatriadi; Sulaiman Musa (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This study aims to analyze the influence of sharia governance and reputation on customer loyalty at Bank Riau Kepri Syariah, both partially and simultaneously. In an effort to maintain customer loyalty, Islamic banks must continuously improve their corporate governance systems to remain competitive compared to other banks. Additionally, Islamic banks are obligated to comply with sharia principles in their instruments, products, operations, practices, and management. This research employs a quantitative approach by distributing questionnaires to 100 customers. The data were analyzed using linear regression methods with the assistance of IBM-Statistic software. The results indicate that both sharia governance and reputation variables, individually and collectively, have a positive and significant impact on customer loyalty. These findings suggest that the implementation of good sharia governance and a positive reputation can enhance customer loyalty at Bank Riau Kepri Syariah.